In Vivo Evaluation of Propex Electronic Apex Locator - Özsezer, E.; Inan, U.; Aydin, U. (Elsevier Science Inc, 2007)
The aim of this in vivo study was to evaluate the performance of ProPex apex locator after extirpation and in presence of different irrigation solutions: 2.5% NaOCl, 0.9% NaCl, and 0.2% chlorhexidine gluconate solutions. Twenty-seven single-rooted human teeth scheduled for extraction with mature apices were selected for this study. Measurements were performed by using ProPex after extirpation and in presence of the irrigation solutions. After extraction of the teeth, a stereomicroscope was used to confirm visually the relationship of the tip of the endodontic file to the apical foramen, and actual lengths (ALs) were determined by reducing 0.5 mm from these lengths. The data were statistically analyzed with cluster analysis. The results of this study showed that measurements after extirpation had the smallest distance to the ALs. Among the irrigation solution groups, chlorhexidine gluconate group had the smallest distance to the ALs, whereas saline group had the greatest. Most accurate measurements were obtained after extirpation. © 2007 American Association of Endodontists.
Keywords: Apex Locators; Irrigation Solutions; Propex